2020
DOI: 10.3390/nu13010101
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in Breast Milk Fatty Acids Contents: A Case Study of Malay Breastfeeding Women

Abstract: The composition of human breast milk changes in the first two months of life, adapting itself to the evolving needs of the growing new-born. Lipids in milk are a source of energy, essential fatty acids (FA), fat-soluble vitamins, and vital bioactive components. Information on breast milk FA of Malaysian lactating women is scarce. Based on convenience sampling, a total of 20 Malay breastfeeding women who fulfilled the inclusion criteria were recruited. Breast milk was collected three times from each subject at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 37 publications
1
13
1
Order By: Relevance
“…In addition, the median HM ARA/total fat of 0.60% in our cohort was higher compared to the global average (0.55 %), leading to a higher ARA/DHA ratio (3.24) when compared to that reported in the literature (1.5 -2) (37). The HM n-6/n-3 fatty acid ratio in our study (mean 10.57), while comparable to some geographies, was higher than others (38), suggesting differences either in body fat composition and mobilization of fat stores or dietary habits such as consumption of LA-rich vegetable oils (39). Levels of most PLs (PC and PE) in our study were comparable to those reported from Singapore (32).…”
Section: Hm Nutrients In the First Six Postnatal Monthssupporting
confidence: 85%
“…In addition, the median HM ARA/total fat of 0.60% in our cohort was higher compared to the global average (0.55 %), leading to a higher ARA/DHA ratio (3.24) when compared to that reported in the literature (1.5 -2) (37). The HM n-6/n-3 fatty acid ratio in our study (mean 10.57), while comparable to some geographies, was higher than others (38), suggesting differences either in body fat composition and mobilization of fat stores or dietary habits such as consumption of LA-rich vegetable oils (39). Levels of most PLs (PC and PE) in our study were comparable to those reported from Singapore (32).…”
Section: Hm Nutrients In the First Six Postnatal Monthssupporting
confidence: 85%
“…In addition, the median human milk ARA of 0.60% in our cohort was higher compared with the global average (0.55 %), leading to a higher ARA/DHA ratio (3.24) when compared with that reported in the literature (1.5–2) ( 47 ). The human milk n-6/n-3 fatty acid ratio in our study (mean 10.57), while comparing some geographies, was higher than others ( 48 ), suggesting differences in either body fat composition and mobilization of fat stores or dietary habits such as consumption of LA-rich vegetable oils ( 49 ). The levels of most PLs (PC and PE) in our study were comparable to those reported from Singapore ( 42 ).…”
Section: Discussioncontrasting
confidence: 58%
“…It could be speculated that the dietary deficiency of these essential FA early in life in WD‐pups may contribute to the inappropriate programming and development of these animals, which is in accordance with the metabolic alterations observed in WD‐pups at mid lactation. Moreover, ALA is precursor of the long‐chain n‐3 PUFA EPA (C20:5) and DHA (C22:6), [ 32 ] whose proportions were also decreased in the milk of WD‐dams. It has been previously described that maternal obesity induced by a high‐fat diet also causes, among other changes, a reduction in the levels of EPA and DHA in milk.…”
Section: Discussionmentioning
confidence: 99%